Web Accessibility for Developers (Open textbook library., 2019)
Web Accessibility for Developers is a technical book aimed primarily at programmers. Learn how to develop accessible interactivity on the Web and gain expertise using WAI-ARIA, a W3C specification that enables optimal use of assistive technologies, like screen readers, when navigating the Web.